Malignant PEComa With Metastatic Disease at Diagnosis and Resistance to Several Chemotherapy Regimens and Targeted Therapy (m-TOR Inhibitor). (September 2017) - Machado, Isidro; Cruz, Julia; Lavernia, Javier; Rayon, José M.; Poveda, Andrés; Llombart-Bosch, Antonio
Perivascular epithelioid cell tumors (PEComas) are infrequent neoplasms with peculiar myomelanocytic differentiation. The aggressive abdominopelvic variant is rare, with only a small number of published cases. We present an additional case of this unusual variant, which showed an aggressive histologic and clinical behavior with multiple liver metastases and resistance to several therapies. We also discuss the histological and immunohistochemical profiles as well as the differential diagnosis.